Determination of Drying Kinetics of Tunceli Garlic with Microwave Drying Technique - Hakan Yoğurtçu (Journal of Agricultural Sciences)
In this study, drying kinetics of 4 mm-thick slices of Tunceli garlic Allium tuncelianum was investigated by using microwave technique at an interval of 90-600 W microwave output power. Ten mathematical models were used to represent the experimental data in this study. The determination of coefficient R2 , root mean square error RMSE , chi-square χ2 and percentage error E% values that show compatibility to these models were determined. The determination of coefficient R2 values were found to vary at an interval of 0.9440-0.9993. The Midilli et al model was determined to be the best model that represents the experimental data. It was seen that drying rate increases with the increase in microwave output power P and decreases with the increase in sample mass m . Effective diffusion coefficients Deff and drying rate constants k were determined for different sample masses at microwave output power of 90 W. Activation energies for both effective diffusion coefficients and drying rate constants were determined by using an Arrhenius type exponential equation. Activation energies from effective diffusion coefficients and drying rate constants were found as 3.85 W g-1 and 3.99 W g-1 respectively.